Misinterpretation of Some Islamic Teachings and Traditions as Gender Discrimination Against Women - Sulaiman, Kamaldeen Olawale (INSANCITA, 2016)
ABSTRACT: This paper examines the misinterpretation of some Islamic teachings and traditions which are erroneously regarded as gender discrimination against women with a view to addressing them in consonance with Islamic rulings or practices. It examines why Islam prescribed veil, dress code for women; polygamy that the voice of women should not be heard by men; women stay behind men in prayer; and waiting/mourning period for women. The method for this research is purely written sources, including documents, monographs, manuscripts, books, journals, internet, magazines as well as the holy book of Al-Qurâan and Al-Hadith. The paper revealed that the âhijabâ helps to safeguard the modesty and decency of a person and safeguards the moral ideals of a society. Also, during congregational prayer, Muslims stand side by side maintaining closeness by standing foot to foot, shoulder to shoulder, and demonstrating brotherhood and sameness in status. If men and women should stand in this position, it is impossible for them to attain full concentration due to difference in sexes. Also, Islam prescribes waiting period for widow to ascertain whether the woman is pregnant for the deceased husband. It is the Muslims themselves, through their ill practice of their religion, who give impetus to such misinterpretations. Thereafter, concluded that, as for Islam, gender equality is part of its jurisprudence and fundamental teachings.KEY WORD: Misinterpretation, Islamic teachings and traditions, gender discrimination, veil, polygamy, prayer, mourning period for women, and Islamic jurisprudence and fundamental teachings.ABSTRAKSI: âSalah Tafsir Beberapa Ajaran dan Tradisi Islam tentang Diskriminasi Gender terhadap Perempuanâ. Makalah ini mengkaji salah tafsir beberapa ajaran dan tradisi Islam yang dianggap keliru mengenai diskriminasi gender terhadap perempuan yang bermaksud untuk memberikan kesesuaian dengan aturan atau praktek Islam. Ia mengkaji mengapa Islam menganjurkan jilbab, etika berpakaian untuk perempuan; poligami bahwa suara perempuan tidak harus didengar oleh laki-laki; perempuan berada di belakang laki-laki dalam shalat; dan masa menunggu untuk wanita dalam berkabung. Metode dalam penelitian ini adalah sumber murni tertulis, termasuk dokumen, monograf, naskah, buku, jurnal, internet, majalah, serta dari kitab suci Al-Qurâan dan Al-Hadits. Makalah ini mengungkapkan bahwa âhijabâ membantu untuk menjaga kesopanan dan kesusilaan seseorang dan menjaga cita-cita moral masyarakat. Juga, selama shalat berjamaah, umat Islam berdampingan menjaga kedekatan dengan berdiri dari kaki ke kaki, bahu ke membahu, dan menunjukan persaudaraan dan kesamaan status. Jika laki-laki dan perempuan harus berdiri dalam posisi berdampingan, ini tidak mungkin bagi mereka untuk mencapai konsentrasi penuh karena perbedaan jenis kelamin. Juga, Islam mengatur masa tunggu bagi janda untuk memastikan apakah kehamilan wanita itu karena suaminya yang sudah almarhum. Adalah umat Islam sendiri, melalui salah amalan dalam agama mereka, yang memberikan dorongan untuk salah tafsir tersebut. Karenanya, disimpulkan bahwa kesetaraan gender merupakan bagian dari hukum dan ajaran-ajaran fundamental dalam Islam. KATA KUNCI: Salah tafsir, ajaran dan tradisi Islam, diskriminasi gender, jilbab, poligami, shalat, masa berkabung bagi perempuan, serta hukum dan ajaran fundamental Islam.About the Author: Kamaldeen Olawale Sulaiman, Ph.D. is a Lecturer at the Department of Religious Studies ESU (Ekiti State University) in Ado-Ekiti, Nigeria. For academic purposes, the author can be contacted via GSM No. 08068298472 or via e-mail at: drsulaimanko@yahoo.comHow to cite this article? Sulaiman, Kamaldeen Olawale. (2016). âMisinterpretation of Some Islamic Teachings and Traditions as Gender Discrimination Against Womenâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.1(1), February, pp.1-16. Bandung, Indonesia: Minda Masagi Press, ISSN 2443-1776. Chronicle of the article: Accepted (June 4, 2015); Revised (December 19, 2015); and Published (February 5, 2016).